Leaf-mining Nepticulidae (Lepidoptera) from record high altitudes: documenting an entire new fauna in the Andean páramo and puna - Stonis, Jonas R.; Diškus, Arūnas; Remeikis, Andrius; Gerulaitis, Virginijus; Karsholt, Ole (Zootaxa, 2016)
The monograph treats 29 species of leaf-mining pygmy moths (Insecta, Lepidoptera, Nepticulidae) discovered in the northern Andean bush and grass páramo and the central Andean puna at altitudes above 3700 m. They represent the world’s highest-altitudinal Nepticulidae fauna known. The height record belongs to Stigmella nivea sp. nov. from Peru collected at an elevation of 4700 m. Except for one species, all belong to Stigmella Schrank. Twenty-two of the species recorded are new and are named and described in the current paper: Stigmella paramica Diškus & Stonis, sp. nov.; S. lachemillae Diškus & Stonis, sp. nov.; S. gynoxyphaga Diškus & Stonis, sp. nov.; S. calceolariae Diškus & Stonis, sp. nov.; S. rigida Diškus & Stonis, sp. nov.; S. altiplanica Diškus & Stonis, sp. nov.; S. robusta Remeikis & Stonis, sp. nov.; S. pseudorobusta Remeikis & Stonis, sp. nov.; S. auriargentata Remeikis & Stonis, sp. nov.; S. altimontana Remeikis & Stonis, sp. nov.; S. pandora Remeikis & Stonis, sp. nov.; S. ampla Diškus & Stonis, sp. nov.; S. evanida Diškus & Stonis, sp. nov.; S. mustelina Remeikis & Stonis, sp. nov.; S. angusta Diškus & Stonis, sp. nov.; S. alticosma Remeikis & Stonis, sp. nov.; S. nivea Remeikis & Stonis, sp. nov.; S. kristenseni Diškus & Stonis, sp. nov.; S. lobata Remeikis & Stonis, sp. nov.; S. ageratinae Diškus & Stonis, sp. nov.; S. clinopodiella Diškus & Stonis, sp. nov.; and S. calceolarifoliae Diškus & Stonis, sp. nov. Some of these species are leaf-miners on Asteraceae (Pentacalia, Baccharis, Gynoxys, and Ageratina plants), Calceolariaceae (Calceolaria), Lamiaceae (Clinopodium), and Rosaceae (Lachemilla). Twenty species are known only from adults with no data on their biology and host-plants. In addition, we present data and discuss recently discovered nepticulid taxa associated with Polylepis forests that is the natural vegetation in much of the High Andes. All High-Andean Stigmella species treated are illustrated with photographs of the adults and genitalia, distribution maps, including some with photographs of the leaf-mines and habitats.